Radioprotective Effect Of Alcoholic Extract Of Mentha Piperita (Linn) On Swiss Albino Mice Exposed To Whole Body Gamma Irradiation: A Preliminary Study - PALLAVI KAUSHIK; MEGHA MATHUR; NEHA RAWAT; PUNAR DUTT (International Journal of Pharma and Bio Sciences, 2012)
Natural Products offer an alternative to synthetic radioprotectors being less toxic. In this study 50% alcoholic extract of Mentha piperita (ALM) was tested for its radioprotective ability in terms of radiation sickness and survival of Swiss albino mice. This drug was well tolerated at highest dose of 1000mg/kg b.wt./day for three consecutive days. All doses of drug provided significant protection against radiation sickness and mortality, however the highest protection was observed at 100mg/kg. The optimum dose of 100mg/kg b.wt./day was determined on the basis of maximum survival and biochemical analysis of lowest lipid peroxidation and highest reduced glutathione levels. To determine the dose reduction factor (DRF) the optimum dose was administered for three consecutive days before 6,8,10 Gy gamma irradiation and 30 day survival was studied simultaneously with radiation sickness. The LD50/30 value of experimental (ALM + irradiation) was found to be considerably higher (8.052 ±0.115) than irradiation alone (5.598±0.09) group. On the basis of LD 50/30 survivability, ALM pretreatment produced a dose reduction factor (DRF) of 1.44.